Dependent capitalisms in contemporary Latin America and Europe - Madariaga, Aldo; Palestini, Stefano (Stefano Emilio Ignacio Palestini Cespedes) (Switzerland : Palgrave Macmillan, 2021)
This book contributes to the current revival of dependency approaches for the analysis of global capitalism. Reflecting on contemporary uses of the (3z(BDependency Research Program(3y (B(DRP) and a refined analytical toolkit, it makes two distinctive contributions to this revival: the analysis of new (3z(Bsituations of dependency(3y(B, and the understanding of the (3z(Bmechanisms of dependency(3y(B. The individual chapters draw from a wide range of cases and data from Latin America and Europe and imbricate concepts and ideas from the DRP with those of other approaches, from post-Keynesian economics to structural economics, institutional economics, regulation theory, comparative capitalisms, business politics, economic geography and critical finance studies, providing a rich array of possibilities for virtuous inter-disciplinary cross-fertilization. This volume is a valuable contribution for those interested in understanding how global capitalism works in Latin America, Europe and beyond.s
Includes bibliographical references and index.
Keywords: Capitalism -- Latin America